Evaluation of composite action in cross laminated timber-concrete composite beams with CFRP reinforcing bar and plate connectors using Digital Image Correlation (DIC). (1st April 2021) - Hadigheh, S.A.; McDougall, R.; Wiseman, C.; Reid, L.
Highlights: New composite shear connectors are proposed for timber-concrete composite beams. Structural behaviour of FRP bar/plate is compared with steel plate/screw system. Composite behaviour in TCC beams is investigated using a DIC-based technique. Steel plate and FRP bar illustrated highest bending stiffness and composite action. CFRP rebar and steel screw TCC beams demonstrated highest ultimate load. Abstract: This research proposes new types of shear connectors made of carbon fibre reinforced polymer (CFRP) composites for effective stress transfer between the timber and concrete sections in cross laminated timber (CLT)-concrete composite beams. New shear connectors are designed and made of bidirectional carbon fibre reinforced polymer (CFRP) composite plates and crossed CFRP reinforcing bars. The mechanical performance, bending stiffness, ductility, and interfacial slippage and strain of timber-concrete composite (TCC) beams with CFRP connectors are compared with those with steel plate and screw systems through four-point flexure testing. Local slip, interfacial slip and strain behaviour are comparatively analysed for connections with equivalent axial stiffness using a Digital Image Correlation (DIC) based technique, so that relative composite behaviour could be determined. Furthermore, a cost evaluation is undertaken to compare the feasibility of proposed shear connectors for construction of TCC systems. Results from flexural tests demonstrate that CFRP rod specimens experience higher ultimate load and bending stiffness in elastic loading stage and ductility in failure while slippage at serviceability and ultimate load is minimal. These results demonstrate that CFRP reinforcing bars can be used as an alternative to existing steel plate/screw systems. Although CFRP plate connectors show lower ultimate strength, bending stiffness and ductility, the performance of the system can be further improved by using sufficient anchorage systems at the end of CFRP plate within the concrete.